The Safety Assessment of Chemical Grouting “Sodium Silicate-based” in Indonesian Soils - Rizky Satria Putranto; Hideki Shimada; Imam Achmad Sadisun; Masyhur Irsyam; Sugeng Wahyudi; Tomohiko Abe (Himpunan Ahli Teknik Tanah Indonesia, 2023)
Chemical grouting is a method to improve or accelerate the solidification process on a loose soil. The implementation of improper chemical grouting may lead to affect the safety level of groundwater; thus, the technical ability and safety should be analyzed comprehensively to prevent degenerative effect on environment. Volcanic soil is targeted on this research coherent to the abundancy in Indonesia. In this study, a field scale test was conducted to validate leaching test results that were obtained in the lab and to confirm the safety of sodium silicate-based chemical grouting. In addition, the geoelectric survey was conducted to ensure the flowing of groundwater by observing resistivity of soil layer. On laboratory test result, the significance basic pH was observed, in consequence some test revealed an increase in concentration of heavy metals. The bench test was conducted in Jatinangor area’s soil as a representative of Indonesian soil to validate the laboratory result. During the bench test, the pH of ground water was monitored continuously for 5 months, where a slight increase in the pH values of ground water was observed. In addition to that, water samples were collected and analyzed in the laboratory to examine heavy metal contamination in ground water on the 18th day after the chemical grouting injection was started. However, the increased concentration was not found which indicates the pH control shall be the main control of metal leaching. As the conclusion, pH monitoring as early measurement for chemical grouting effect on groundwater is proposed to be set as standard for chemical grouting work.